Security of wireless keyboards: threats, vulnerabilities and countermeasures - Jovanović, Siniša V.; Protić, Danijela D.; Antić, Vladimir D.; Grdović, Milena M.; Bajić, Dejan A. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: This paper provides an overview of research on computer system vulnerabilities caused by compromised electromagnetic radiation by wireless keyboards. Wireless devices that use event-triggered communication have been shown to have critical privacy issues due to the inherent leakage associated with radio frequency emissions. Wireless connectivity technology is a source of signal emanation that must be protected in terms of performance and security.Methods: Wireless device vulnerabilities and side-channel attacks are observed, along with electromagnetic emission of radio waves.Results: The findings highlight a specific wireless keyboard's security and encryption flaws. The results of penetration testing reveal vulnerabilities of targeted wireless keyboards in terms of outdated firmware, encryption, wireless reliability, and connection strength.Conclusion: Wireless keyboards have security flaws that disrupt radio communication, giving a malicious user complete access to the computer to which the keyboard is connected. An attacker can steal sensitive data by observing how the system works using compromised electromagnetic emissions.
Keywords: wireless keyboard; radio frequency; electromagnetic emission; software defined radio